Pharmacological Evaluation of Cucumis Sativus Linn Fruits Extract For Anti Anxiety And Antidepressant Activity In Experimental Rats - Mehta, Roshan Kuma; Shrestha, Sushan; Mehta, Vivek Kumar; Thapa, Shankar (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Depression and anxiety are common mental health disorders, with a lifetime prevalence of 10% in the general population. Cucumis sativus mostly contain alkaloids, glycosides, terpenoids, ﬂavonoids, tannin used for its diabetic, purgative, skin disease, ulcer protective, laxative, anthelmintic effect. The present study was designed to extract the chemical constituents and evaluation of anti-anxiety and antidepressant activity of Cucumis sativus fruits using experimental rats. MATERIAL AND METHODS The fruits of the Cucumis sativus plant were collected and chemical constituents were extracted by ethanol as solvent. Wistar rats of 150-250 gram were taken as study animal into four groups. Anti-anxiety and antidepressant activity were performed by Elevated plus maze and Forced swim test in Wistar rat. The ethanolic extract of low dose (250 mg/kg) and high dose (500 mg/kg) were subjected for anti-anxiety and antidepressant activity. RESULTS In the elevated plus maze as animal models of anxiety, extract treated 500 mg/kg showed more effective than 250 mg/kg in both time spent and number of entry in open arm but decrease in close arm as compared to control group (p<0.05). In forced swim test as an animal model of depression, extract treated 250 and 500 mg/kg produce signiﬁcant reduction (p<0.05 and p<0.001 respectively) in the immobility period. The extract 500 mg/kg was found to be similar to that of standard drug imipramine (p<0.001). CONCLUSION The present study concludes that the extract possesses potent and sustained anti-anxiety and antidepressant activity of Cucumis sativus fruits.